Níveis de metilação do gene MTHFR e sua relação com níveis glicêmicos, estresse oxidativo e estilo de vida em indivíduos adultos: um estudo de base populacional - Lima, Keylha Querino de Farias (2018)
After the completion of the genome project, new research lines emerged, among them a nutrigenomics, whose objective is to relate the dietary components to the human genome. From this report you should be ready to analyze the epidemic mechanisms, which are developing and are not metabolizable. DNA methylation is the most sensitive and participatory mechanism of transcriptional transmission of gene expression, with variables related to metabolic and health disorders. Changes in methylation of the MTHFR gene lead to changes in the homocysteine and folic acid cycle. In addition, the enzyme methylenetetrahydrofolate reductase is encoded by this gene can make methyl groups for a methylation of DNA. The aim of this study was to evaluate the methylation levels of the MTHFR gene and to correlate glycemic levels, oxidative stress and lifestyle in adult individuals. This is a population-based cross-sectional epidemiological study involving 265 adult individuals in the age range of 20 to 59 years of both genders, representative of the East and West Zones of the city of João Pessoa / PB. Population-based research entitled "II Cycle of Diagnosis and Intervention of Food, Nutrition and Non-Communicable Diseases of the Population of the Municipality of João Pessoa / PB". The data were newborns through epidemiological applications, lifestyle, evaluation of food consumption and nutritional status. From the blood samples were found serum concentrations of total antioxidant capacity, malondealdehyde, lipid profile, folic acid, vitamin b12 and homocysteine, were analyzed. DNA methylation levels analyzes in the promoters of the MTHFR gene were performed by the real-time PCR method. For statistical analysis, linear regression using STATA 13 was used. The methylation levels of the MTHFR gene were 34.14% ± 17.41. The equilibrium between the methylation class with fasting blood glucose levels, when fasting blood glucose increases 1mg / dl, methylation levels increased by 0.050% and the relation with the eventual consumption of more than six doses of alcoholic beverage in the most generic is the larger size compared to serum levels of methylation increased by 4.47%. It was already used for folate consumption, a low to reverse, that is, as folate consumption decreased by 1mg, methylation levels increased by 0.05%. It is concluded that the data demonstrate a positive association between methylation of the MTHFR gene, fasting glucose and alcohol consumption in a series of events, and negative for folate consumption.